Resolution of the Expert council “Unsolved problems of targeted therapy for paroxysmal nocturnal hemoglobinuria in Russia” - A. D. Kulagin; E. A. Lukina; V. V. Ptushkin; M. P. Kostinov; E. G. Arshanskaya; T. N. Babaeva; T. I. Ksenzova; Z. T. Fidarova; M. V. Marchenko (Онкогематология, 2023)
On June 24, 2023, an Expert Council was held in St. Petersburg, during which leading experts in the field of hematology discussed current achievements and answered a number of unresolved issues of targeted therapy of paroxysmal nocturnal hemoglobinuria (APG) in order to further improve treatment results in Russia. During the Expert Council, the following aspects of targeted APG therapy were considered: • criteria for the suboptimal response of patients with APG to therapy with inhibitors of the 5th component of complement (C5); • efficacy and safety of the use of pegcetacoplan in APG in patients with insufficient efficacy of inhibitors of the C5 component of complement; • vaccination issues before starting therapy with complement inhibitors and the possibility of conducting treatment with pegcetacoplan at home.